The Grammatical Accuracy, Cohesion and Coherence of Thai Students’ English Writing at Darawithaya School, Narathiwat – Thailand - Ruqoyyah Amilia Andania (IJET (Indonesian Journal of English Teaching), 2017)
Writing has been recognized as an important skill to be mastered by all students both English as Foreign Language (EFL) and English as Second Language (ESL) students since many universities around the world offer writing courses. Hence, this study attempts to analyze the grammatical accuracy, cohesion, and coherence of Thai Students’ English Writing at Darawithaya School. This study is designed to investigate (1) the grammatical accuracy on Students’ Writing, and (2) the cohesion and coherence on Students’ Writing. The participant of the study consists of 14 Second Grade Students of Senior High School who enroll Academic Education at Darawithaya School, Narathiwat – Thailand. Since this study is descriptive qualitative approach, the data is documentation from students’ writing work. Some guidelines and rubric are used in this research for analyzing. The findings reveal that there are 73 errors are found on 14 students’ composition in this study. They occur on singular/plural followed by subject omission, the use of article, pronoun, preposition, verb omission, S-V agreement, word formation, tense, and extraneous subject. Consequently, those errors make students’ grammatical accuracy value varied from one student to other students.